Pemberdayaan Masyarakat Menghadapi Perkembangan Destinasi Ekowisata di Kecamatan Suoh Kabupaten Lampung Barat - Nadya Amalia Nasution; Ibrahim Besar; Vito Frasetya; Siti Samhati (Jurnal PkM (Pengabdian kepada Masyarakat), 2023)
Developing the tourism sector in various regions certainly benefits the local community. Such beautiful and exotic nature makes the area valuable and unique. On the other hand, local indigenous people must also be able to survive and keep up with changes in tourism development in their area. The method used is counseling and simulation. This service tries to explore and study social communication problems, primarily business communication, that occurs in communities in remote areas. Problems in society, the first is the lack of understanding of the proper and correct post-harvest processing of agricultural and plantation products; the second is the lack of knowledge of the importance of establishing MSMEs and the use of legal brands and third, the forestry and tourism departments have not entirely given the trust in tourism management. , even though the local community has made a significant contribution to the forestry department financially by inviting forest encroachers to come down the mountain. The result of this service activity is that there is a need for entrepreneurship assistance to the community and government of Suoh District, especially Suka Marga Village, as an area that directly impacts tourism objects, which aim to increase independence and welfare. Legal assistance is also needed so that the community and local government have a better understanding of the law.